PERSEPSI DAN ASPIRASI MASYARAKAT PESANTREN TERHADAP PENYIAPAN ULAMA MELALUI PESANTREN: STUDI KASUS DI DELAPAN KOTA - Husen Hasan Basri (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2007)
The aim of this research is to describe pesantren communio's perception and aspiration in preparing of ulama through pesantren education. The research was conducted in eight locations, namely, Medan, Agam, Lampung, Ciamis, Brebes, Kediri, Banjarmasin, and Balikpapan. The method was a quantitative approach and the instruments for collecting data used were questionaire for pesantren community (ustack and santri) and non pesantren community (formal leader, informal leader, and religion bureaucrats), and interview guidance for pesantren leaders. It is found that pesantren community still perceived that pondok pesantren is regarded as the most e ective institution for preparing the ulama.